Pengaruh Kualitas Produk Dan Brand Trust Terhadap Keputusan Pembelian Mobil Toyota Kijang Innova (Studi Pada Recall Kijang Innova Cikarang) - Diah Permata Ega Lestari; Reminta Lumban Batu (Universitas Hamzanwadi, 2022)
One of the popular transportation used is a car. There are many types of cars that are created according to needs, some are designed to transport goods with a large capacity, transport people with a certain capacity, and so on. Increasingly, companies that produce cars, especially private cars, are competing to launch sophisticated products and attract the attention of the public, both in terms of technology and usefulness. on purchasing decisions of Toyota Kijang Innova, to determine the simultaneous effect of Product Quality and Brand Trust on purchasing decisions of Toyota Kijang Inova. The method in this study uses quantitative methods with descriptive and verification approaches. The population in this study are car users in West Java, with the sample technique used is Non-Probability with the type of sample technique using Purposive Sampling so that the sample used is 100 samples. The data analysis technique used is path analysis. The results of this study are partial testing to get the results that there is a partial positive effect of Product Quality on Purchase Decisions of 0.912, there is a partial influence of Brand Trust on Purchase Decisions of 0.942. Simultaneous testing got the results that Product Quality and Brand Trust had a positive effect on purchasing decisions.